Kepentingan Venezuela Untuk Membuka Kembali Foreign Direct Investment (FDI) Dari Chevron - Uitsi Bevugni, Ni Made Ovsamtena; Wiranata, I Made Anom; Prameswari, A.A.Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRAK Venezuela nationalize d the assets that had been managed by the multinational corporations (MNC). However, Venezuela decide to keep the relations between the MNC s by making negotiations with th em. One of the MNCs that responded to the negotiation is Chevron which was the only American company involved in the negotiation. The purpose of this study is to describe the interests of Venezuela to reopen foreign direct investment from Chevron. This study examined the concept of national interest and foreign policy. National interest is affected by economic, ideology and the power . While, foreign policy is affected by economic and ideology factors . This research used descriptive qualitative method and library research in the data collecting. The delimitation of this research is between 2007 to 2013. This study found that Venezuelan interest to reopen FDI from Chevron was influenced by the interests of Venezuela to improve the life of its people through increas ing production, preventing decrease in production through exploration, benefiting from technology transfer, increas ing exports, encourag ing work opportunities, and improving the experience of Venezuela student through internship program . Chevron also contributed to the growth of education, economic development, health, and cultural in Venezuela. Keywords : Foreign Direct Investment, Venezuela, Chevron, National Interest